The evolution of high-alumina basalts of the Klyuchevskoy volcano, Kamchatka, Russia, based on microprobe analyses of mineral inclusions - Ozerov Alexei Y. (My University, 2000)
The origin of calc-alkaline high-alumina basalts (HAB) of the Klyuchevskoy volcano, Kamchatka, was examined using electron microprobe analyses of phenocrysts and mineral phases included in the phenocrysts. Continuous trends on major-element variation diagrams suggest the HAB were derived from high-magnesia basalt (HMB) by fractional crystallization. Phenocrysts in the HAB are strongly zoned: olivine (Mg# 91–64), clinopyroxene (Wo45–38En40–51Fs5–20) and chrome—spinel/magnetite inclusions in them (Cr2O3 45–0 wt.%, TiO2 0.5–11%). Microprobe analyses of minerals included in the phenocrysts provide additional constraints on the mineral crystallization trends in the HAB. Fe/Mg partitioning data, when applied to the phenocrysts cores, show they crystallized from a HMB. The similarity of phenocryst core compositions in HAB with those in HMB strongly suggests a genetic relationship between the two magma types.
Keywords: 38.37.25 Вулканология; Ключевской